The Effectiveness of Health Promotion on the Prevention of Urolithiasis: Narrative Literature Review - Yogi Bisma Widawasista; Irma Seliana; Wayan Dhea Agastya (Jurnal Kesehatan dan Kedokteran, 2026)
Urolithiasis remains a significant public health problem due to its high recurrence rate and strong association with lifestyle-related risk factors, such as inadequate hydration and unhealthy dietary habits. Preventive efforts through health promotion are therefore essential, not only to reduce recurrence but also to support broader public health goals, including the achievement of Sustainable Development Goal (SDG) 3. Objective: This study aimed to review the effectiveness of health promotion interventions in preventing urolithiasis between 2020 and 2025 and to examine their contribution to achieving SDG 3. Method: This study employed a narrative literature review design using secondary data from articles published between 2020 and 2025. The literature was retrieved from Google Scholar, GARUDA, and university journal portals. Selected studies were analysed descriptively and thematically to identify the types of health promotion interventions and their reported outcomes in urolithiasis prevention. Findings: The review showed that health promotion interventions were effective in improving knowledge, attitudes, and preventive behaviours related to urolithiasis. Community-based and school-based programs increased awareness of adequate hydration, healthy dietary patterns, and water-consumption habits, demonstrating their positive contribution to prevention efforts. Implications: These findings suggest that health promotion is a practical and cost-effective strategy for preventing urolithiasis and may also support broader non-communicable disease prevention initiatives aligned with SDG 3. The integration of digital health approaches is recommended to strengthen program sustainability and encourage long-term behavioural change. Originality: This review provides a focused synthesis of post-2020 evidence on preventive health promotion strategies for urolithiasis. Its value lies in extending the discussion beyond clinical management by offering context-specific insights that contribute to public health practice and preventive health policy.